Analysis of microstructural evolution and mechanical properties of FGH101 powder superalloy and IN718 deformed superalloy via inertia friction welding - Zhou, Jun; Zhang, Yongqiang; Qin, Feng; Zhang, Xuelong; Wang, Hao; Liu, Ze; Zhang, Wenhan; Huang, Caiyan; Zhang, Chunbo (Frontiers in Materials, 2025)
Nickel-based superalloys are indispensable in aerospace engines due to their exceptional high-temperature strength, oxidation resistance, and corrosion resistance, making them critical for joining processes such as inertia friction welding (IFW), which is favored for its efficiency and superior joint quality. In this study, IFW was used to join FGH101 powder superalloy with IN718 deformed superalloy, resulting in significant plastic deformation that formed symmetrical ear-shaped flash on the IN718 side and minor upsetting on the FGH101 side, with a wavy interface due to heat dissipation. Microhardness analysis revealed higher hardness at the weld interface, followed by a sharp decline near the Heat Affected Zone (HAZ) on the IN718 side due to phase re-dissolution, while FGH101 showed quicker recovery. Post-weld aging treatments enhanced hardness and strength through γ′ and δ phase precipitation in FGH101 and γ″ phases in IN718. Room temperature tensile tests demonstrated impressive strength with failures occurring plastically within the IN718 base metal, whereas elevated temperatures shifted failure locations to the weld zone without necking. Fatigue tests exhibited varied lifespans, with fractures initiating either at stress concentrators or within the FGH101 base metal far from the weld center. Scanning electron microscope (SEM) analysis confirmed mixed-mode fracture patterns, underscoring the importance of microstructure on joint performance and suggesting that optimizing IFW parameters can lead to superior weld quality in aerospace components, thus providing valuable insights for future research and industrial applications.